1997
DOI: 10.1246/bcsj.70.993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Properties of Vanadium Nitrides

Abstract: Vanadium nitride catalysts were synthesized by the temperature-programmed reduction of vanadium oxide (V2O5) with pure NH3. The resulting materials contained VN or VN with a negligible amount of vanadium sesquioxide (V2O3) in the bulk after the nitrization of V oxides, indicating that the structural properties of these materials were strong functions of the heating rate and space velocity employed. The V nitrides proved to be active NH3 decomposition catalysts. Since the activity varied with changes in the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…The temperatures used for vanadium ,, and niobium , were taken from previous studies; the surface areas obtained are close to those reported in the literature. The synthesis of Ta 3 N 5 from Ta 2 O 5 has been previously reported under isothermal conditions , at 1170 K. Figure shows the XRD of the products of ammonia TPRe of L-Ta 2 O 5 at various temperatures (the final product at 1070 K had a surface area of 72 m 2 g -1 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The temperatures used for vanadium ,, and niobium , were taken from previous studies; the surface areas obtained are close to those reported in the literature. The synthesis of Ta 3 N 5 from Ta 2 O 5 has been previously reported under isothermal conditions , at 1170 K. Figure shows the XRD of the products of ammonia TPRe of L-Ta 2 O 5 at various temperatures (the final product at 1070 K had a surface area of 72 m 2 g -1 ).…”
Section: Resultssupporting
confidence: 69%
“…Some of the methods developed for synthesizing high surface area carbides and nitrides include gas-phase reactions of metal compounds, reaction of gaseous reagents with solid-state metal compounds, ,, pyrolysis of metal precursors 45 and solution reactions. , Among these, one of the most promising and widely used is the temperature-programmed method (TPRe) developed by Boudart and co-workers. Nearly all the work to date has concentrated on the synthesis of carbides and nitrides of molybdenum and tungsten, with the exception of iron catalysts for Fischer−Tropsch chemistry, with very little work being done on the other metals, ,, and even less on mixed metal systems, , despite the promise shown by these systems. Therefore, the TPRe method of synthesis has been further investigated for the synthesis of binary and ternary early transition metal carbides suitable for catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the VN catalyst showed superior activity with respect to Ni/Al 2 O 3 −SiO 2 . 353 Also, the tantalum carbide TaC showed a good activity, comparable to that obtained using the other nitrides and carbides. 354 Finally, using Fe 3 C iron carbide, Kraupner et al 355 obtained good ammonia conversion and high stability at 600 °C.…”
supporting
confidence: 53%
“…The results showed that the carbides of the two elements are more active for the decomposition of the ammonia. However, the VN catalyst showed superior activity with respect to Ni/Al 2 O 3 –SiO 2 . Also, the tantalum carbide TaC showed a good activity, comparable to that obtained using the other nitrides and carbides .…”
Section: Catalysts For the Thermal Decomposition Of Ammoniamentioning
confidence: 58%
“…The catalytic activity of molybdenum carbide materials is found to strongly related to their surface structure and elemental composition, which, in turn, depend on the method of synthesis. Some of the procedures developed for synthesizing high surface area molybdenum carbide materials include gas-phase reactions of volatile metal compounds, reaction of gaseous reagents with solid-state metal compounds, ,, pyrolysis of metal precursors, and solution reactions. , Among these, one of the most promising and widely used is the gas-phase carburization of molybdenum oxides, developed by Boudart and co-workers. However, there are many carbon sources for this carburization reaction, and it has become apparent that various carbon sources and conditions bestow different properties, structure, and catalytic performance on the resulting carbides. ,, To date, most of the work has focused on the use of mixtures of hydrogen and methane or ethane as carburizing agents. However, these gas mixtures are relatively unreactive and require the use of relatively high temperatures to affect carburization.…”
Section: Introductionmentioning
confidence: 99%